The Executive Statutes of the general sales Tax Law = اللائحة التنفيذية لقانون الضريبة العامة على المبيعات - Egypt. Ministry of Finance. The Egyptian Customs Authority (2025)
Ch1 Preliminary provisions -- Ch2 Assessment and accrual of the tax -- Ch3 Assessment of the value -- Ch4 Bills, declarations, notifications, books, and registers -- Ch5 Registration -- Ch6 Deduction, exception from, and refund of the tax -- Ch7 Collection of the tax -- Ch8 Control -- Ch9 Miscellaneous provisions -- Ch10 General provisions -- Ch11 Transitional provisions